Learning Styles, Brain Dominance, Emotional Intelligence, and Second Language Learning Motivation and Anxiety in Secondary Students - Ershadi Manesh, Soudabeh (Health Nexus, 2026)
The present study aimed to determine the relationship between learning styles, brain quadrant dominance, and emotional intelligence with anxiety and enthusiasm for second language learning among male and female students in lower and upper secondary schools in Alborz Province. In terms of purpose, this research was applied, and in terms of data collection, it was descriptive and correlational in nature. The statistical population included all lower and upper secondary school students in Alborz Province during the 2023–2024 academic year. A multistage cluster sampling method was used to select the sample, and 300 students were ultimately chosen as participants. Data were collected using standardized questionnaires, including Kolb’s Learning Styles Questionnaire (1985), Bradberry and Greaves’ Emotional Intelligence Questionnaire (2004), Herrmann’s Brain Dominance Instrument (1980), and Knowles et al.’s Second Language Learning Questionnaire (2000). The collected data were analyzed using inferential statistical methods, including correlation coefficients and multiple regression analysis, through SPSS version 26. The findings indicated that learning styles, brain quadrant dominance, and emotional intelligence had a significant negative relationship with amotivation in second language learning at the 0.05 significance level (p < .05). Furthermore, a significant positive relationship was found between learning styles, brain quadrant dominance, and emotional intelligence with both intrinsic and extrinsic motivation for second language learning at the same significance level (p < .05). In addition, the results showed that learning styles, brain quadrant dominance, and emotional intelligence respectively explained 68% of the variance in amotivation, 68% of the variance in intrinsic motivation, and 73% of the variance in extrinsic motivation for second language learning among students.